Why Katz is Wrong: A Lab-Created Creature Can Still Have an Ancient Evolutionary History. Issue 2 (4th May 2022) - Campbell, Douglas Ian
ABSTRACT: Katz denies that organisms created in a lab as part of a de-extinction attempt will be authentic members of the extinct species, on the basis that they will lack the original species' defining biological and evolutionary history. Against Katz, I note that an evolutionary lineage is conferred on an organism though its inheriting genes from forebears already possessed of such a lineage, and that de-extinction amounts to a delayed, human-assisted reproductive process, in which genes are inherited from forebears long dead. My conclusion is that de-extinct organisms can perfectly well have an ancient evolutionary history, contrary to Katz's assumption.